Efficacy and safety of ReDuNing injection as a treatment for COVID-19 and its inhibitory effect against SARS-CoV-2. (28th October 2021) - Ma, Qinhai; Xie, Yuqi; Wang, Zhoulang; Lei, Biao; Chen, Ruihan; Liu, Bin; Jiang, Haiming; Wang, Yutao; Liu, Qingquan; Yang, Zifeng
Abstract: Background: Although the rapid emergence of coronavirus disease 2019 (COVID-19) poses a considerable threat to global public health, no specific treatment is available for COVID-19. ReDuNing injection (RDN) is a traditional Chinese medicine known to exert antibacterial, antiviral, antipyretic, and anti-inflammatory effects. In addition, RDN has been recommended in the diagnosis and treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-associated pneumonia by the National Health Council and the National Administration of Chinese Medicine. However, there is no information regarding its efficacy against COVID-19. Aim of study: This study was designed to determine the clinical efficacy of RDN in patients with COVID-19 and characterize its antiviral activity against SARS-CoV-2 in vitro . Materials and methods: A total of 50 adults with COVID-19 were included in this study, and the primary endpoint was recovery from clinical symptoms following 14 days of treatment. General improvements were defined as the disappearance of the major symptoms of infection including fever, fatigue, and cough. The secondary endpoints included the proportion of patients who achieved clinical symptom amelioration on days 7 and 10, time to clinical recovery, time to a negative nucleic acid test result, duration of hospitalization, and time to defervescence. Plaque reduction and cytopathic effect assays were also performed in vitro, and reverse-transcription quantitative PCR was performed to evaluate the expression of inflammatory cytokines (TNF-α, IP-10, MCP-1, IL-6, IFN-α, IFN-γ, IL-2 and CCL-5) during SARS-CoV-2 infection. Results: The RDN group exhibited a shorter median time for the resolution of clinical symptoms (120 vs. 220 h, P < 0.0001), less time to a negative PCR test result (215 vs. 310 h, P = 0.0017), shorter hospitalization (14.8 vs. 18.5 days, P = 0.0002), and lower timeframe for defervescence (24.5 vs. 75 h, P = 0.0001) than the control group. In addition, time to improved imaging was also shorter in the RDN group than in the control group (6 vs.8.9 days, P = 0.0273); symptom resolution rates were higher in the RDN group than in the control group at 7 (96.30% vs. 39.13%, P < 0.0001) and 10 days (96.30% vs. 56.52%, P = 0.0008). No allergic reactions or anaphylactic responses were reported in this trial. RDN markedly inhibited SARS-CoV-2 proliferation and viral plaque formation in vitro . In addition, RDN significantly reduced inflammatory cytokine production in infected cells. Conclusions: RDN relieves clinical symptoms in patients with COVID-19 and reduces SARS-CoV-2 infection by regulating inflammatory cytokine-related disorders, suggestion that this medication might be a safe and effective treatment for COVID-19. Graphical abstract: Image 1